The bioactivity profile of the fractions from the ethanol extract of Derris elliptica Benth ("Tubli") leaves - Uy, Mylene M.; Deguino, Rhosa Veca D. (2015)
The bioactivites and potential medicinal properties of te leaves of Derris elliptica Benth were investigated by evaluating the toxicity, antioxidant and antimicrobial activities of its hexane (DeH), chloroform (DeC) and aqueous (DeA) fractions. Results show that the DeA fraction exhibited chronic toxicity against the brine shrimp. The DeC fraction was shown to have the highest antioxidant potentials in terms of total antioxidant activity and total phenolics content. In terms of total antioxidant activity and total phenolics content. In terms of radical-scavenging activity, both DeC and DeA results also demonstrated that the DeC fraction exhibited antioxidant activites but it was not toxic. For antimicrobial activities, DeH, DeC and DeA fractions were partially active towards S.aureus, A. niger and B. subtilis. Furthermore, DeA fraction was very active against S. aureus.
Keywords: Medicinal plants; Toxicology; Antioxidants